Cytotoxic Activity of Acinetobacter baumannii after Treatment with Aminoglycosides - Hoštacká, Anna; Kováčiková, Zuzana (Arzneimittelforschung, 1999)
The effect of three aminoglycoside antibiotics – netilmicin (CAS 56391-57-2), gentamicin (CAS 1403-66-3) and amikacin (CAS 37517-28-5) – at subinhibitory concentrations (sub- MICs; ¼ or 1/16 of the MICs) on the cytotoxic activity of Acinetobacter baumannii was studied. The cytotoxic factor was manifested by reduction of the number of isolated rat lung type II cells evaluated by alkaline phosphatase determination. All aminoglycosides at both concentrations studied (with the exception of ¼ of the MIC of amikacin) did not modify cytotoxic activity of A. baumannii. This activity was partially inhibited only after treatment with amikacin at ¼ of the MIC. In this case the number of type II cells after incubation with antibiotic treated A. baumannii was higher (71%) as compared to the number of type II cells cultured with untreated A. baumannii (47%).
Keywords: Acinetobacter baumannii, cytotoxic activity, rat lung type II cells; Amikacin; CAS 1403-66-3; CAS 37517-28-5; CAS 56391-57-2; Gentamicin; Netilmicin